Pencegahan Penyalahgunaan Minuman Keras Pada Siswa Melalui Edukasi Peningkatan Pengetahuan - Winnellia Fridina Sandy Rangkuti; Sudarto Sudarto; Susito Susito; Sarliana Zaini; Jada Jada (WASATHON Jurnal Pengabdian Masyarakat, 2024)
Liquor is any type of drink that contains alcohol and addictive substances harmful to the body. Alcohol abuse is one of the serious problems after the abuse of addictive substances and drugs. Alcohol abuse is allegedly prevalent among students, students, and even young executives. The school/college environment is thought to be the main environment for high drinking. The purpose of this activity is to provide education about liquor abuse. The method used in this activity by conducting tests (pre test and post test), before and after counseling is carried out to assess the level of knowledge or understanding of students about alcohol abuse as an indicator of the success of a health promotion program. The results of counseling showed that there was an increase in students' knowledge or understanding of liquor abuse, from 35 to 95 percent. Based on the results of this assessment, students are expected to better understand the handling and prevention of liquor abuse.